Phototactic Behavioral Responses of Mesozooplankton in the Barents Sea as an Indicator of Anthropogenic Impact - Dyomin, Victor; Morgalev, Yuri; Morgalev, Sergey; Davydova, Alexandra; Kondratova, Oksana; Morgaleva, Tamara; Polovtsev, Igor (Water (Basel), 2023)
The behavioral responses of autochthonous organisms have recently been used for a system to monitor the state of fresh and sea waters for bioindication. The advantage of using the behavioral responses of mesozooplankton is determined by the higher sensitivity of such responses compared with changes in the composition of biota or the death of organisms. Earlier, we developed and tested in laboratory conditions and in freshwater reservoirs a submersible digital holographic camera as part of a hydrobiological probe, which allows one to determine the dimensions, shape and recognition of plankters in situ, as well as define the concentration of plankters in the working volume and perform photostimulation with attractive radiation with different levels of illuminance. This paper presents the data obtained during the expedition to the Barents Sea. The variability with regard to the immersion depth of the phototropic response and the interspecific and intraspecific diversity was determined. It was shown that within the framework of natural variability in natural factors (temperature, salinity, hydrostatic pressure, oxygen content, illumination) there are no reliable changes in the indicator response, unlike changes in the concentration of plankton associated with tidal currents. The anthropogenic distortion of water quality was modeled by introducing a saturated salt solution dropwise. There were no significant changes in the intraspecific and interspecific diversity index during the external impact, and the rhythms of tidal changes in the concentration of plankters were suppressed. The fact of increased phototropic sensitivity in crustaceans with a size of less than 120 μm was found. It was established that the most essential marker of the alternating factor was the suppression of the phototropic response. The identified patterns of behavioral responses of autochthonous zooplankton make it possible to create a network of continuous control over the environmental health of water bodies subject to increased anthropogenic impact (oil production zones beyond the Arctic Circle, estuaries and deltas of rivers carrying industrial waste).